Protective Effects of Rosuvastatin on Kidney in Experimental Hypertension Rats Models - Onat, Elif; Türk, Ahmet; Kocaman, Nevin (My University, 2023)
Purpose: Hypertension is responsible for approximately 30% of patients who reach end-stage renal disease. Statin is known to reduce the risk of developing kidney disease. In this study, the changes in caspase-3 and fibrillin1 in the kidney tissue of rats with hypertension using L-NAME were investigated along with how rosuvastatin affected the changes caused by hypertension on these proteins. Materials and Methods: 18 Wistar Albino male rats weighing 200-220 g were used in the study. The rats were divided into 3 groups with 6 animals in each group (1.Control, 2.Hypertension, 3.Rosuvastatin).To induce hypertension, rats were given L-NAME for 7 weeks. After the second week, rosuvastatin was given by oral gavage for 5 weeks. Blood pressure values were evaluated on days 0, 14, 28, 42. At the end of the experiment, all rats were sacrificed and caspase-3 and fibrillin1 levels were evaluated. Results: Blood pressures were found to be higher in the hypertension group on the 14th, 28th, and 42nd days (p=0.001). Rosuvastatin caused a decrease that was found to be insignificant at 28th, 42nd days. Caspase-3 (p=0.001), fibrillin1 (p=0.001) immunoreactivity were found to be increased in the hypertension group. Compared with the hypertension group, caspase-3 (p=0.031), fibrillin1 (p=0.030) immunoreactivity were decreased in the rosuvastatin group. However, caspase-3 (p=0.036) and fibrillin1 (p=0.041) immunoreactivity was increased in the rosuvastatin group compared to the control group. Conclusion: Although rosuvastatin didn’t significantly decrease blood pressure, it is thought that caspase-3 and fibrillin1 may mediate its protective effect on hypertensive kidneys.
Keywords: L-NAME; statin; caspase-3; fibrillin-1